Evidence and Impacts of Nanoplastic Accumulation on Crop Grains. Issue 33 (17th October 2022) - Jiang, Meng; Wang, Binqiang; Ye, Rui; Yu, Ning; Xie, Zhenming; Hua, Yuejin; Zhou, Ruhong; Tian, Bing; Dai, Shang
Abstract: Nanoplastics are emerging pollutants of global concern. Agricultural soil is becoming a primary sink for nanoplastics generated from plastic debris. The uptake and accumulation of nanoplastics by crops contaminate the food chain and pose unexpected risks to human health. However, whether nanoplastics can enter grains and their impact on the grains of crop grown in contaminated soil is still unknown. Here, the translocation of polystyrene nanoplastics (PS‐NPs) in crops, including peanut ( Arachis hypogaea L.) and rice ( Oryza sativa L.) is investigated. It is demonstrated PS‐NPs translocation from the root and accumulation in the grains at the maturation stage. The treatment with PS‐NPs (250 mg kg −1 ) increases the empty‐shell numbers of rice grain by 35.45%, thereby decreasing the seed‐setting rate of rice by 3.02%, and also decreases the average seed weight of peanuts by 3.45%. Moreover, PS‐NPs exerted adverse effects on nutritional quality, such as decreasing the content of mineral elements, amino acids, and unsaturated fatty acids. To the knowledge, this is the first report of the presence of nanoplastics in the grains of crop plants grown in soil containing nanoplastics, and the results highlight the impact of nanoplastics on the yield and nutritional quality of crop grains. Abstract : This study demonstrates that polystyrene nanoplastics could accumulate in crop grains, and pose adverse effects on nutritional quality of crop grains. Considering the ubiquitous distribution of plastic debris, the uptake and accumulation of nanoplastics by crops can contaminate the food chain, pose negative impacts on the crop economy and also may bring unexpected risks to human health.